2020
DOI: 10.33545/26633329.2020.v2.i2a.53
|View full text |Cite
|
Sign up to set email alerts
|

Deal exclusivity in cross-cultural e-commerce

Abstract: The purpose of this paper was to investigate the effect of deal exclusivity on accommodation booking intention, with regard to both hedonic and utilitarian aspect of the offer. Also, the role of cultural background was examined to see whether the consumers from different cultures response to deal exclusivity differently. In an experimental survey, a total of 208 persons participated (113 persons from the Netherlands and 95 persons from Vietnam). They judged an online advertisement of a room accommodation (an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Lee et al (2021) found a positive impact between indulgence orientation and attitude toward Airbnb use. Since consumers with indulgence‐orientated values do not feel guilty about satisfying themselves, they have hedonic motives, and their spending tendencies increase (Broeder & Nguyen, 2020). In addition, studies show indulgence positively affects online shopping expenditure (Yıldırım, Arslan, & Barutçu, 2016).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Lee et al (2021) found a positive impact between indulgence orientation and attitude toward Airbnb use. Since consumers with indulgence‐orientated values do not feel guilty about satisfying themselves, they have hedonic motives, and their spending tendencies increase (Broeder & Nguyen, 2020). In addition, studies show indulgence positively affects online shopping expenditure (Yıldırım, Arslan, & Barutçu, 2016).…”
Section: Analysis and Resultsmentioning
confidence: 99%